Which cost of debt should be used in forecasting cash flows? (2009)
Frequently, analysts and teachers use the capitalized rate of interest for the cost of debt when forecasting and discounting cash flows. Others estimate the interest payments when forecasting annual financial statements or cash flows based on the average of debt calculated with the beginning and ending balance. Others use the end of year convention that calculates the yearly interest multiplying the beginning balance times its contractual cost. The use of one or other methods is critical for the definition of the tax savings. These approaches are illustrated with examples and the differences in using them. A simple proposal to solve the problem is presented.